Trends and gender disparities in the burden of rheumatoid arthritis in Pakistan from 1990 to 2021 - Hong Cheng; Tao Li; Canxuan Li; Wei Su (Scientific Reports)
Abstract Rheumatoid arthritis (RA) significantly drives global morbidity and mortality, yet its evolving impact in low- and middle-income countries remains underexplored. This study harnesses extensive global burden of disease (GBD) data to delineate the temporal trends of RA burden in the Islamic Republic of Pakistan from 1990 to 2021, examine its association with socio-demographic development, and forecast future trajectories through 2036. This retrospective epidemiological study quantified RA disease metrics in Pakistan through GBD data interrogation. Joinpoint regression modeling delineated temporal trajectories, calculating average annual percent change (AAPC) with 95% confidence intervals (CIs). Spearman’s rank correlation assessed the relationship between socio-demographic index (SDI) values and age-standardized rates (ASRs) of RA across 204 regions. A Bayesian age–period–cohort (BAPC) model was employed to project RA burden trends in Pakistan from 2022 to 2036. Stratified comparative assessments revealed age- and sex-specific demographic disparities. Although age-standardized incidence rate (ASIR) and age-standardized prevalence rate (ASPR) exhibited modest declines (AAPC: -0.10% and − 0.09%, respectively), the absolute numbers of incident and prevalent RA cases increased markedly—from 8,606 to 19,454 and from 134,628 to 318,963, respectively—between 1990 and 2021. Mortality rates showed a slight upward trend (AAPC: 0.35%), with total deaths rising from 478 to 1,006, while Disability-adjusted life years (DALYs) nearly doubled, increasing from 27,314 to 62,774. Age-specific analyses revealed peak incidence among younger individuals (20–24 years) and higher mortality and DALYs among older populations, particularly those aged 75 and above. Additionally, females consistently experienced a greater burden across all metrics compared to males. SDI exhibited significant positive correlations with ASIR (r = 0.42), ASPR (r = 0.47), age-standardized mortality rate (ASMR) (r = 0.32), and age-standardized DALYs rate (ASDR) (r = 0.46; all p < 0.001), indicating that higher socio-demographic development was associated with a greater documented RA burden. BAPC projections forecast a gradual decline in age-standardized RA rates through 2036, although absolute case numbers are expected to remain high owing to population growth and demographic aging. The RA burden in Pakistan has escalated over the past three decades, with higher-SDI regions demonstrating disproportionately greater age-standardized rates and documented cases. Despite anticipated per-capita declines in RA incidence, prevalence, mortality, and DALYs by 2036, demographic shifts will likely sustain a substantial absolute burden. These findings emphasize the necessity of precise public health measures to advance early diagnosis, optimize disease management, and reinforce prevention—particularly in rapidly developing areas and among high-risk groups such as women and the elderly.